LOCAL WISDOM OF JEMBER COMMUNITY IN REDUCING CYANOGENIC LEVELS TO LOWER URINE THIOCYANATE LEVELS - Farida Wahyu Ningtyias; Ahmad Husain Asdie; Madarina Julia; Yayi Suryo Prabandari (UNEJ e-Proceeding)
Disorders caused by iodine deficiency remains aglobal health problem in the world with a prevalenceof 30.6% in 2007 (De Benoist et al., 2003; De Benoistet al., 2008). The causing factors are not only limitedto iodine deficiency. Instead, other factors of IDD aregoitrogenic substances; one of them is thiocyanateresulted from cyanide detoxification. The workmechanism of thiocyanate disrupts thyroid functionby inhibiting the uptake of the iodine and interfereswith the thyroid peroxidase (TPO) activities (Gaitan,1990; Taurog, 1970; Van Etten, 1969; Stoewsand,1995; Virion et al., 1980 cit Chandra & Ray, 2001;Chandra et al., 2004; Delange, 2000; Erdogan, 2003;Gibbs, 2006; Sinebeeh, 2007; Semba & Delange,2008). In addition, small amount of cyanide is alwaysavailable in many kinds of plants commonlyconsumed by community. Goitrogenik source foodsare easily accessible by the community because theprices are cheap or they can be self-planted (Nio,1989; Chandra et al., 2004).Some studies mention that most of the goitrogenicsubstances do not cause clinical effects except theyare going along with iodine deficiency. Therefore,the consumption of goitrogenic substances becomesetiologic agent in an endemic area (Zimmermann etal., 2008). Jember is one of regencies in East Javawhich experiences an increase in TGR from 21.94%in 2003 to 23.57% in 2007. Most of its districts areincluded in the category of endemic goiter area(Jember regency Health Department, 2007). Theresults of previous studies made by the researchersshow that goitrogenic substance as a causativefactor of IDD in Jember, through one of theindicators of urinary iodine levels, is included in thecategory of normal and tend to be high. In addition,urinary thiocyanate levels goiter group are higherthan those in non-goiter group (Ningtyias, 2006;Ningtyias et al., 2007; Ningtyias et al., 2008).Consumption pattern of goitrogenic source food inJember of at least 3-5 times per week with anaverage consumption of 505 μg per day is a riskfactor of IDD in Jember (Megawati, 2007; Ningtyiaset al., 2008). The existence of these substances willdisrupt the process of the formation of thyroidhormones; therefore, it needs to be eliminated, orthe levels are reduced, so that the food ingredientscontaining goitrogenic substances are safe forconsumption. This study used local wisdom to solveproblems of nutrition, that is, one of the habits ofpeople in Jember to boil vegetables for freshvegetables for overcoming nutritional problem ofIDD because the boiling process can reducecyanogenic levels up to 93% (Murdiana, 2001). Bythe decrease in cyanogenic levels, it is expected thatgoitrogenic substance intake into the body willdecrease indicated by the decreasing biomarkers ofgoitrogenic substance of urinary thiocyanate levels.